2017
DOI: 10.3390/ijms18020390
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Gelsolin Induced Glomerular Fibrosis via the TGF-β1/Smads Signal Transduction Pathway in IgA Nephropathy

Abstract: Glomerular fibrosis has been shown to be closely related to the progression and prognosis of IgA nephropathy (IgAN). However, mechanism underlying IgAN glomerular fibrosis remains unclear. Recently, our study showed that plasma gelsolin (pGSN) was decreased in the serum of an IgAN mouse model and that pGSN deposition was found in the glomeruli. Another cytokine, TGF-β1, which is closely related to glomerular fibrosis, was also found to be highly expressed in the glomeruli. In the present study, we report that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…TGF-β 1 signaling pathway mediated by Smad protein plays an important role in the development of tissue fibrosis [44]. Recent studies have shown that the TGF-β 1 / Smad3 signaling pathway is involved in fibrosis in many organs [45,46]. In our study, the data showed that the TGF-β 1 /Smad3 signaling was involved in ovarian tissue fibrosis in POI rats.…”
Section: Discussionsupporting
confidence: 55%
“…TGF-β 1 signaling pathway mediated by Smad protein plays an important role in the development of tissue fibrosis [44]. Recent studies have shown that the TGF-β 1 / Smad3 signaling pathway is involved in fibrosis in many organs [45,46]. In our study, the data showed that the TGF-β 1 /Smad3 signaling was involved in ovarian tissue fibrosis in POI rats.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, we have demonstrated that rhuGSN (0.375-12.5 μg/mL) increases cell viability and promotes fibroblast proliferation, leading to wound healing in 3T3-L1 cells. Our findings are consistent with previous reports demonstrating the proliferative effect of recombinant pGSN on human corneal epithelial cells and mesangial cells [34][35][36]. The rhuGSN also exhibited antioxidant property by protecting the cells from oxidative stress induced by H 2 O 2 exposure.…”
Section: Discussionsupporting
confidence: 93%
“…TGF-β 1 signaling pathway mediated by Smad protein plays an important role in the development of tissue brosis [42]. Recent studies have shown that the TGF-β 1 /Smad3 signaling pathway is involved in brosis in many organs [43][44]. In our study, the data showed that the TGF-β 1 /Smad3 signaling was involved in ovarian tissue brosis in POI rats.…”
Section: Discussionsupporting
confidence: 56%